Effects of exercise on dietary protein requirements - Lemon, P. W. (International Journal of Sport Nutrition and Exercise Metabolism, 1998)
This paper reviews the factors (exercise intensity, carbohydrate availability, exercise type, energy balance, gender, exercise training, age, and timing of nutrient intake or subsequent exercise sessions) thought to influence protein need.